How To Drive Satisfaction Of Simulator Software Users ? - Nur Endah Retno Wuryandari; Christian Rudyyanto; Riki Aprianto; Rahmat Ilahi (DEAL: International Journal of Economics and Business, 2023)
This study aims to examine the role of the Technology Acceptance Model (TAM) on the satisfaction of users of oscilloscope simulator software at the Vocation School of Engineering in Jakarta. This study uses an explanatory research design with quantitative methods. The population in this study were users of the Oscilloscope simulator at the Jakarta Vocational School. The number of samples in this study was 100 respondents. The results of the study indicate that there is a positive and significant effect of perceived ease of use and perceived usefulness on Attitude Toward Using, and Attitude Toward Using has a positive and significant effect on user satisfaction, while perceived ease of use and perceived usefulness have a positive but insignificant effect on user satisfaction. Perceived ease of use not significant on user satisfaction. Also perceived usefulness have not significant on user satisfaction. The path that states the strongest influence relationship is perceived ease of use has a positive effect on perceived usefulness